The Role Of Social Media Marketing And Performance Expectancy On Enrollment Decision At MAN 1 Jepara: Social Media Interaction And Enrollment Intention As Mediating Variables - Lusi Setyani; Ali Ali; Anna Widiastuti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Social Media Marketing is currently one of the most important marketing strategies for both profit and non-profit businesses, including educational institutions or schools. This study aims to analyze the role of social media marketing and performance expectancy on enrollment decisions at MAN 1 Jepara, with social media interaction and enrollment intention as mediating variables, while the analytical tool used was Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that the analysis of the direct influence of social media marketing and performance expectancy on enrollment decisions is proven to be acceptable. Likewise, the indirect influence of the variables of social media interaction and enrollment intention is proven to be acceptable. These findings confirm that madrasah marketing strategies need to emphasize not only the intensity of digital promotions, but also improving the quality of interactions and managing educational performance expectations to encourage prospective students' enrollment decisions. This research provides theoretical implications for the development of educational marketing studies and practical implications for madrasa administrators in designing more effective digital-based student admission strategies